Hormone Replacement Therapy in Cancer Survivors – Review of the Literature - Deli, Tamás; Orosz, Mónika; Jakab, Attila (Pathology oncology research, 2020)
Rapid advance in oncology leads to increasing survival of oncologic patients. More and more of them live long enough to reach either the natural age of menopause or, as a side effect of their oncotherapy, experience the cessation of gonadal function, leading to premature ovarian insufficiency, with disturbing vasomotor symtoms and long-term negative cardiovascular and skeletal effects. Thus, an ever increasing number of cancer survivors search endocrinologic help in the form of hormone replacement therapy (HRT). The misinterpretation of the WHI (Women's Health Initiative) Study has lead to an irrational fear of female hormone replacement, both by the general population and medical professionals. It has seemed the logical and safe conclusion to many physicians to avoid HRT, supposing that this attitude definitely causes no harm, whereas the decision of prescribing estrogen alone or with progestins might bear oncologic and thromboembolic risks and may even lead to litigation in case of a potentially related complication. However, it was known even before the WHI results that premature menopause and hypogonadism decreases the life expectancy of women by years through its skeletal and cardiovascular effects, and this negative effect correlates with the length of the hypoestrogenaemic period. Therefore, the denial of HRT also needs to be supported by evidence and should be weighed againts the risks of HRT. Yet, the oncologic risk of HRT is extremely difficult to assess. In this work we review the latest evidence from in vitro experiments to clinical studies, regarding HRT in survivors of gynecologic and non-gynecologic cancers. Based on our literature research, we group tumours regarding the oncologic risk of properly chosen female hormone replacement therapy in cancer survivors as follows: ’HRT is advanageous’ (e.g. endometrial cancer type I, cervical adenocarcinoma, haematologic malignancies, local cutaneous malignant melanoma, colorectal cancer, hepatocellular cancer); ’HRT is neutral’ (e.g. BRCA 1/2 mutation carriers without cancer, endometrial cancer type II, uterinal carcinosarcoma and adenosarcoma, certain types of ovarian cancer, cervical, vaginal and vulvar squamous cell carcinoma, prolactinoma, kidney cancer, pancreatic cancer, thyroid cancer); ’HRT is relatively contraindicated’ for various reasons (e.g. leiomyosarcoma, certain types of ovarian tumours, brain tumours, advanced metastatic malignant melanoma, lung cancer, gastric cancer, bladder cancer); ’HRT is diasadvantageous and thus contraindicated’ (e.g. breast cancer, endometrial stroma sarcoma, meningioma, glioma, hormone receptor positive gastric and bladder cancer).